Extracellular vesicles carry SARS‐CoV‐2 spike protein and serve as decoys for neutralizing antibodies. Issue 8 (18th June 2021) - Troyer, Zach; Alhusaini, Najwa; Tabler, Caroline O.; Sweet, Thomas; de Carvalho, Karina Inacio Ladislau; Schlatzer, Daniela M.; Carias, Lenore; King, Christopher L.; Matreyek, Kenneth; Tilton, John C.
Abstract: In late 2019, a novel coronavirus named severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) emerged in Wuhan, China. SARS‐CoV‐2 and the disease it causes, coronavirus disease 2019 (COVID‐19), spread rapidly and became a global pandemic in early 2020. SARS‐CoV‐2 spike protein is responsible for viral entry and binds to angiotensin converting enzyme 2 (ACE2) on host cells, making it a major target of the immune system – particularly neutralizing antibodies (nAbs) that are induced by infection or vaccines. Extracellular vesicles (EVs) are small membraned particles constitutively released by cells, including virally‐infected cells. EVs and viruses enclosed within lipid membranes share some characteristics: they are small, sub‐micron particles and they overlap in cellular biogenesis and egress routes. Given their shared characteristics, we hypothesized that EVs released from spike‐expressing cells could carry spike and serve as decoys for anti‐spike nAbs, promoting viral infection. Here, using mass spectrometry and nanoscale flow cytometry (NFC) approaches, we demonstrate that SARS‐CoV‐2 spike protein can be incorporated into EVs. Furthermore, we show that spike‐carrying EVs act as decoy targets for convalescent patient serum‐derived nAbs, reducing their effectiveness in blocking viral entry. These findings have important implications for the pathogenesis of SARS‐CoV‐2 infection in vivo and highlight the complex interplay between viruses, extracellular vesicles, and the immune system that occurs during viral infections.